Antioxidant capacity of phenolic compounds on human cell lines as affected by grape-tyrosinase and Botrytis-laccase oxidation. (15th August 2017) - Riebel, Matthias; Sabel, Andrea; Claus, Harald; Xia, Ning; Li, Huige; König, Helmut; Decker, Heinz; Fronk, Petra
Highlights: Tyrosinase and laccase alter antioxidative capacity of phenolics differently. Oxidation by tyrosinase increased the antioxidant capacity of many phenolic compounds. Oxidation by laccase tended to decrease the antioxidant capacity. Changes in the antioxidant capacity influence quality and health aspects of wine. Importance to consider also the oxidized metabolites of phenolic wine components. Abstract: Phenolic components (PCs) are well-known for their positive impact on human health. In addition to their action as radical scavengers, they act as activators for the intrinsic cellular antioxidant system. Polyphenol oxidases (PPOs) such as tyrosinase and laccase catalyze the enzymatic oxidation of PCs and thus, can alter their scavenging and antioxidative capacity. In this study, oxidation by tryosinase was shown to increase the antioxidant capacity of many PCs, especially those that lack adjacent aromatic hydroxyl groups. In contrast, oxidation by laccase tended to decrease the antioxidant capacity of red wine and distinct PCs. This was clearly demonstrated for p -coumaric acid and resveratrol, which is associated with many health benefits. While oxidation by tyrosinase increased their antioxidant activity laccase treatment resulted in a decreased activity and also of that for red wines.